2018
DOI: 10.1002/elan.201800520
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Determination of Arsenic Using Silver Nanoparticles

Abstract: In the present work, silver colloid was produced by chemical reduction of silver salt (silver nitrate) using citrates in aqueous solution. UV‐Vis spectrophotometry indicated the formation of nanoparticles. The surface plasmon resonance peak in absorption spectra of the silver colloidal solution showed an absorption maximum at 435 nm. The dynamic light scattering and zeta potential measurements showed that the size and the zeta potential of the synthesized nanoparticles were about 98 nm and −50 mV respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…The decreased charge during the CV cycling could be explained by some loss of Ag atoms from the surface, probably in the form of AgCl, or loss of electronic contact between Ag/AgCl and the gold surface, during the CV‐based oxidation/reduction of Ag/AgCl, respectively. Giovanni and Pumera and Ruzgas et al have also observed that charges involved during electrochemistry of AgNPs were decreasing, whereas the number of scans was increasing.…”
Section: Resultsmentioning
confidence: 91%
“…The decreased charge during the CV cycling could be explained by some loss of Ag atoms from the surface, probably in the form of AgCl, or loss of electronic contact between Ag/AgCl and the gold surface, during the CV‐based oxidation/reduction of Ag/AgCl, respectively. Giovanni and Pumera and Ruzgas et al have also observed that charges involved during electrochemistry of AgNPs were decreasing, whereas the number of scans was increasing.…”
Section: Resultsmentioning
confidence: 91%
“…Baudelaire Matangouo Sonkoue generated silver nanocolloids by the chemical reduction of silver salts using citrate in aqueous solution and used a gold electrode modified with silver nanoparticles as the working electrode in linear sweep voltammetry for the detection of arsenic ions. Under optimal conditions, calibration curves were plotted over a concentration range of 0.05–0.2 μM and the limit of detection was estimated to be 13.8 nM [ 112 ]. In addition, composites of silver nanomaterials with chitosan and graphene are also of interest for the electrochemical detection of arsenic.…”
Section: Electrochemical Detection Electrodes For As(iii)mentioning
confidence: 99%
“…Among these metal ions Cu (II) is the major interfering agent because of the formation of intermetallic Cu3As2 species that generate competition for adsorption against As(III). 24 Thus, we analyzed the impact of Cu(II) on the electrochemical sensing efficiency of the CN@ZF-Ms-IL electrode using SWASV under optimized conditions. Figure 4A shows the stripping peak current response of CN@ZF-Ms-IL towards 10 ppb of As(III) in the presence of increasing concentration (20-60 ppb) of Cu(II).…”
Section: Figure 3 25 Selective Efficiency Of the Designed Cn@zf-ms-il Towards As(iii) Monitoringmentioning
confidence: 99%